Perilaku Masyarakat dalam Pemeliharaan Hutan Lindung di Banjar Kedisan, Desa Yehembang Kauh, Kecamatan Mendoyo, Kabupaten Jembrana - PRASADA, I DEWA NGAKAN INDRA; ASTITI, NI WAYAN SRI; HANDAYANI., M.TH. (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Society Behavior On conservation of Protected Forest in the Sub-Village of Kedisan, Yehembang Kauh Village, Mendoyo District, Jembrana Regency. The protected forest will be preserved by the society if the knowledge, attitude and action on the protected forest belong in the category of good and even very good. The aim of this study is to find out the behavior (knowledge, attitude, and action) of the society on conservation of protected forest in Sub-Village of Kedisan, Yehembang Kauh Village, Mendoyo District, Jembrana Regency. This research uses descriptive qualitative method of analysis. Based on the result of the study, it is revealed that people's behavior towards protected forest belongs in the category of ‘good’ in which reach the level of 80,50 %. In the level of knowledge falls into the category of "high" with achieving a score of 80%, for the level of attitudes classified in the category of "agreed" with the achievement score of 80,49 %, and for the level of action classified in the category of "frequent" with achieving a score of 81%. To maximize the level of behavior (knowledge, attitudes, and actions) of the society on the conservation of protected forest, it is advisable to the related government, particularly the Department of Forestry to hold socialization on protected forest as well as giving instructions and certain regulation, either in the form of manuals or bulletin boards. Keywords: protected forests, behavior, society